Renálna retencia mocoviny u oviec - Leng, L; Szanyiová, M (Veterinarni medicina, 1987)
The urea-retaining ability of kidneys of ruminants and returning it back to the blood circulation are important features of the mechanism of nitrogen conservation in the organism. Applying the model of a low-nitrogen diet to sheep we found out the low fractional excretion of urea (FE urea) as a result of increased urea transport capacity in renal tubules. The decrease in the amount of excreted urea by 85% was also accompanied by a reduced glomerular filtration rate (GFR). We tried to verify our hypothesis by the cross-perfusion method that the renal excretion of urea in sheep is regulated by a factor circulating in the blood. We found out that FE urea decreased significantly in the cross-perfused kidney (in sheep on a high-nitrogen diet, connected to sheep on a low-nitrogen diet), without any changes in GFR. Our hypothesis is well-supported by the above result. The kidneys of sheep on low nitrogen diet retain urea through a decrease in the GFR and increased tubular urea transport.
Keywords: hodnoty glomerulární filtrace; dusík; močovina; Diet; dieta; Sheep; zvířata; Kidney; ovce; Nitrogen; Glomerular Filtration Rate; ledviny; Urea; Animals